KONTRIBUSI PROGRAM BIMBINGAN PSIKOSOSIAL BERBASIS COGNITIVE BEHAVIORAL THERAPY (CBT) DALAM MANAJEMEN STRES SISWI ANGKATAN 1 TAHUN 2026 UPTD PSRWTS DINAS SOSIAL PRIVINSI SUMATRA SELATAN - Rizky Amaliyah; Adlina Irwan Nasution (FIP UNIRA MALANG, 2026)
Adolescent girls in social rehabilitation institutions face complex psychological pressures due to traumatic life backgrounds, adaptation demands to new environments, and future anxiety. The psychosocial guidance program based on Cognitive Behavioral Therapy (CBT) was designed to improve stress management skills among students of UPTD PSRWTS Batch 1 of 2026. This activity employed a qualitative approach using DASS-21 assessment, semi-structured interviews, behavioral observation, and six-session CBT interventions including psychoeducation, identification of negative automatic thoughts, cognitive restructuring, behavioral activation, and relaxation techniques. As a strategic output, the “3J” model (Pause-Honest-Action) was formulated as a practical stress management guide. Results showed reduction in somatic complaints such as headaches and muscle tension, increased interpersonal openness, and a shift in thinking patterns from catastrophizing to more rational and optimistic perspectives. These findings confirm that CBT-based psychosocial guidance contributes positively to enhancing mental resilience and psychological well-being of adolescent girls in rehabilitation institutions. Keywords: Cognitive Behavioral Therapy; Stress Management; Adolescent Girls; Psychosocial Guidance; Rehabilitation Institution